IMPROVING HIGH SCHOOL STUDENTS' READING COMPREHENSION THROUGH THE THINK-PAIR-SHARE TECHNIQUE - Muhammad Lutfi Ul Mubin, - (2019)
ABSTRAK Penelitian yg berjudul "Improving High School Students' Reading Comprehension through Think-Pair-Share Technique" ini bertujuan untuk menigkatkan kemampuan membaca pemahaman siswa dan untuk mengetahui respon mereka terhadap teknik tersebut. Metode yang digunakan adalah penelitian tindakan kelas dengan dua instrument, yakni pre-post tes dan kuesioner. Adapun subjek penelitian ini adalah 37 siswa kelas XI IPA 4 SMAN 2 Cimahi. Hasil penelitian menunjukkan bahwa ada peningkatan yang signifikan dari membaca pemahaman siswa. Hal ini dapat dilihat dari peningkatan skor rata-rata pre-test (47,43), post-test I (66,33), dan post-test II (75,8). Selain itu, berdasarkan hasil analisis kuesioner juga ditemukan bahwa ada tanggapan positif dari siswa mengenai teknik yang diterapkan. Oleh karena itu, dapat disimpulkan bahwa teknik think-pair-share dapat meningkatkan pemahaman membaca siswa kelas sebelas SMAN 2 Cimahi dan subjek juga menunjukkan bahwa mereka memiliki respons positif terhadap teknik ini. Kata kunci: meningkatkan, membaca pemahaman, think-pair-share ABSTRACT This study entitled "Improving High School Students' Reading Comprehension through Think-Pair-Share Technique" aims to investigate whether the think-pair-share technique could improve students' reading comprehension and to identify the students' responses about the think-pair-share technique in improving reading comprehension. Action research was employed with two instruments namely pre-post tests and questionnaire. The subjects of this study are 37 students of class XI IPA 4 SMAN 2 Cimahi. The result shows that there was a significant improvement of the students' reading comprehension. It can be seen from the improvement of the mean score of the pre-test (47.43), post-test I (66.33), and post-test II (75.8). Moreover, based on the result of analysis of the questionnaire it was also found that there were positive responses from the students regarding the technique applied. Therefore, it can be concluded that think-pair-share technique could improve the reading comprehension of the eleventh grade students of SMAN 2 Cimahi and the subjects indicated that they had positive responses to the technique. Keywords: improving, reading comprehension, think-pair-share.